Nilai-nilai Adab Bersosial dalam Surah An-Nur - Yusuf, Muhammad Suaidi; Mumtaz, Thoriq (Sekolah Tinggi Ilmu Ushuluddin Wadi Mubarak Bogor, 2020)
The loss of adab is a core problem that Muslims must fix today. Among the manners that must get more attention in this day and age are social manners, because humans are not only individual creatures but also social beings who need other people in living their lives. The Qur'an as the main guideline for Muslims in carrying out their religious laws has explained several adabs that are closely related to social etiquette, among the letters that contain social values ​​are Surah An-Nūr. This research was conducted using library research, namely research by examining written sources, for example books or books related to the subject matter of Sayyid Qutb. The approach that the author uses is historical analysis. The author then makes the book Fī Zhilāl Al-Qur'ān as a primary data source and books related to adab as a secondary source. The results of this study found that Sayyid Qutb interpreted 27-32 letters of An-Nūr with the Adāb Ijtmā'ī approach which is easier to understand and practice today. The values ​​of social etiquette contained in verses 27-32 are asking for permission, saying greetings and respecting the privacy of the house, lowering the gaze and maintaining the genitals, avoiding tabarruj in dress, avoiding ikhtilāt between men and women, virtues and motivations for marriage. Everything requires at least two sources for the process to occur. These three verses make Him not have anything similar or comparable to Him in every aspect whatsoever, as in the fourth verse. Second, Ibn Taimiyah refuted the arguments of Jews, Christians, and philosophers with the third verse of Surah Al-Ikhlāṣ. As for the scholars of kalam, he denied them for using a new term in religion to understand religion. Abstrak Hilangnya adab (Loss of adab) merupakan masalah inti yang harus diperbaiki umat Islam pada zaman sekarang. Di antara adab yang mesti mendapatkan perhatian lebih di zaman sekarang adalah adab dalam bersosial, karena manusia bukan hanya makhluk individual akan tetapi dia juga makhluk sosial yang membutuhkan orang lain dalam menjalani kehidupannya. Al-Qur’an sebagai pedoman utama umat Islam dalam menjalankan syariat agamanya telah menerangkan beberapa adab yang berkaitan erat dengan adab bersosial, di antara surat yang mengandung nilai-nilai adab bersosial adalah surat An-Nūr. Penelitian ini dilakukan dengan menggunakan metode kepustakaan, yaitu penelitian dengan cara mengkaji sumber-sumber tertulis, misalnya kitab atau buku yang berkaitan dengan pokok pembahasan yakni Sayyid Quthb. Pendekatan yang penulis gunakan ialah analisis historis. Penulis kemudian menjadikan kitab Fī Zhilāl Al-Qur’ān menjadi sumber data primer dan buku-buku yang berkaitan dengan adab sebagai sumber sekundernya. Hasil penelitian ini menemukan bahwa Sayyid Quthb menafsirkan 27-32 surat An-Nūr dengan pendekatan Adāb Ijtmā’ī yang mana hal tersebut lebih mudah dipahami serta dipraktekan pada zaman sekarang. Nilai-nilai adab bersosial yang terkandung dalam ayat 27-32 adalah Meminta izin, mengucapkan Salam dan menghormati privasi rumah, Menundukan pandangan dan memelihara kemaluan, Menjauhi tabarruj dalam berpakaian, Menghindari ikhtilāt antara laki-laki dan perempuan, Keutamaan dan motivasi menikah.